IMMUNOLOGICAL RESPONSE CHARACTERISTICS IN INDIVIDUALS WITH OVERLAPPING BRONCHIAL ASTHMA AND CHRONIC OBSTRUCTIVE PULMONARY DISEASE (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This study addresses the immunological characteristics of patients with asthma, COPD, and their overlap (ACO). A correlation analysis involving ten clinical and immunological indicators was performed, and based on the relationship between IL-8 and IFN-γ, a prognostic index was developed to assess the likely course of bronchial asthma and COPD overlap. This index enables prediction of disease progression and supports the selection of appropriate therapeutic strategies.